Methodological bases kazakh philosophy (Journal of Philosophy Culture and Political Science, 2015)
The article presents an analysis of the methodological bases of research of the Kazakh national philosophy. Features of outlook and philosophical heritage studied through the prism of epistemological problems, rooted in the long history of culture and spirituality of the Kazakh people. The attention is focused on the challenges and priorities of the study of tradition and modern trends in the Kazakh philosophy, exemplifyregula- tion of relations between people, based on universal ethical principles of the spiritual world of the Kazakhs. Development of culture, philosophy, traditions and customs is directly dependent on the socio-economic and socio-political development. In conclusion, substantiated the urgency of philosophical understanding of the modern world in the context of the differentiation of philosophy from these forms of social consciousness like mythology, religion, ideology.
Keywords: Philosophy; Kazakh philosophy; methodology; history of philosophy; spirituality; ethics.